Methyl 2-naphthoates from a traditional Chinese herb Morinda officinalis var. officinalis. Issue 27 (5th July 2019) - Yu, Jin-Hai; Zhai, Hui-Juan; Yu, Zhi-Pu; Zhang, Qian-Qian; Ge, Yong-Xi; Zhang, Yu-Ying; Jiang, Cheng-Shi; Zhang, Hua
Abstract: Fifteen methyl 2-naphthoate derivatives (1 –15 ), including 11 previously undescribed ones (1 –10 and13 ), have been isolated from the roots of a well-known Chinese herb, Morinda officinalis var. officinalis . The structures of these isolates were determined on the basis of detailed spectroscopic analyses, and 12 of them were identified as six pairs of enantiomers (1 –12 ). While the relative configurations of1 and5 were confirmed by X-ray crystallographic analysis and calculated 13 C NMR data, respectively, the absolute configurations of1 –12 were established via interpretation of experimental and computed ECD data. Compounds1 –4 possessed a novel heterocylic bridge ring system incorporating a 2, 6-dioxabicyclo[3.2.1]oct-3-ene motif. Our biological evaluations revealed that (−)-mornaphthoate E (9 ) showed significant cytotoxicity against a panel of human cancer cell lines (MDA-MB-231, MCF-7 and A549, IC50 1–10 μM), while (−)-mornaphthoate A (2 ) displayed mild inhibition against butyrylcholinesterase (IC50 37.98 ± 1.98 μM). Graphical abstract: Image 1